1996
DOI: 10.1127/lr/11/1996/61
|View full text |Cite
|
Sign up to set email alerts
|

Water quality changes in the Yugoslav part of the Danube river

Abstract: The paper describes specific changes in the quality of the Danube river water due to backwater effects in the Hydropower Plant Dj erdap I and II (Iron Gate I and II) storage reservoirs. The analysis includes changes in the content of suspended matter and turbidity, organic matter, oxygen regime and changes in the composition and abundance of plankton. This reservoir system differs from natural lake systems by a considerable oxygen deficit, especially pronounced during the period of autumn low-water flow, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…; Perisic et al. ; Brezeanu & Cioboiu ; Oguz & Gilbert ; Dokulil & Donabaum ). Future studies should be focused on resolving the influence of these factors on the observed trends in fish catch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Perisic et al. ; Brezeanu & Cioboiu ; Oguz & Gilbert ; Dokulil & Donabaum ). Future studies should be focused on resolving the influence of these factors on the observed trends in fish catch.…”
Section: Discussionmentioning
confidence: 99%
“…Without the expansion of fishing grounds, overall fishing pressure would have resulted in an even more pronounced decline of the mean catch-weighted trophic level (Kleisner & Pauly 2011). However, information regarding potential increases in the primary productivity in the Middle Danube over the studied period is not clear, as well as the complex influence of the construction of dams in the Iron Gates area and the consequent reduction of water flow in the upstream river section (Cociasu et al 1996;Perisic et al 1996;Brezeanu & Cioboiu 2006;Oguz & Gilbert 2007;Dokulil & Donabaum 2014). Future studies should be focused on resolving the influence of these factors on the observed trends in fish catch.…”
Section: Discussionmentioning
confidence: 99%